DISHONESTY IN CELESTE NG’S EVERYTHING I NEVER TOLD YOU - Monica Umboh; Elizabeth Z. Oroh; Agustine C. Mamentu (Program Studi Pendidikan Bahasa Inggris, 2022)
The study was done in the purpose of revealing the dishonesty in Celeste Ng’s Everything I Never Told You. In this study, qualitative research was used because the data are presented in the form of quotation or description. Primary Source is the source of data as in the novel entitled Celeste Ng’s Everything I Never Told You. The secondary sources are documents and internet browsing . This study used objective approach in analyzing data. It means that this study was only focused on dishonesty found only in the novel as written, not in general. The result shows the dishonesty throughout the story. Marilyn assumed her daughter was a scientist, James thought she had a exclusive community of girlfriends, and Nath thought she had a sexual relationship with Jack all of which turn out to be untrue. These roots of lies are developed and become apparent in their actions and words as well. At the time when Lydia’s body is found in the local lake, the delicate balancing act that has been keeping the Lee family together tumbles into chaos, forcing them to confront the long-kept secrets that have been slowly pulling them apart. James, consumed by guilt, sets out on a reckless path that may destroy his marriage. Regardless of the motives owned, lying is an act of manipulation of data that is done consciously so that the other party believes what people say